Relationship between the clinical and Moyers-Jenkins methods for the evaluation of dental crowding - Raquel Bibiana Comas Mirabent; Jacqueline De la Cruz Prieto; Elizabeth Díaz Cedeño; Carlos Carreras Martorell; Manuela Ricardo Reyes (Centro Provincial de Información de Ciencias Médicas, 2015)
A descriptive and cross-sectional study of 29 plaster cast of the lower arch  that  presented a degree of crowding  was carried out, which belonged to patients admitted in the  Orthodontics Department of  "Mártires del Moncada" Teaching Provincial Stomatological Clinic  in Santiago de Cuba, from October to December, 2013, in order to determine the correspondence among the clinical and Moyers-Jenkins methods for the evaluation of  dental crowding.  Among the analyzed variables there were: methods of evaluation of crowding, teething type and degree of dental crowding.  When analyzing the 2 methods those affected with severe discrepancy prevailed; however, most of those that were evaluated as slight discrepancy by the first method were without discrepancy when applying the second one.  Higher precision existed between both methods in the moderated and severe discrepancies.